Syngas production via dry reforming of methane over Nibased catalysts - Farooqi, A.S. (Institute of Physics Publishing, 2020)
Dry reforming of methane (DRM) is emerging as an enticing research area due to the crucial requirement to mitigate global environmental issues and offers as an alternative energy resource. However, the DRM commercialized prospect and industrial utilization are curbed due to the weak prospect of sustained activity of the catalysts. The objective of this research is to find out the effects of the addition of CeO2 and La2O3 as promoters on the performance of the catalyst. In this work, catalysts such as Ni/Al2O3, Ni/Al2O3-CeO2, Ni/Al2O3-La2O3 were prepared by sol-gel method. The prepared catalysts have been characterized by XRD, BET analysis, and temperature-programmed reduction (TPR). BET results revealed that the addition of CeO2 and La2O3 slightly decreased the BET surface area of the synthesized catalyst because of the deposition on the porous structure of the support and filling its pores. The performance of the catalysts in DRM at 800Â°C shows that catalyst with CeO2 have the highest and stable conversion, while La2O3 has a significant role towards the stability of the reaction during the 8 h reaction on stream. Â© Published under licence by IOP Publishing Ltd.